Learner Motivation and Engagement in Virtual EFL Classes at the Tertiary Level in Bangladesh during the Pandemic - Nishat Tasneem (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
In the face of the ongoing pandemic crisis in the country, the tertiary level education context of Bangladesh has predominantly resorted to online and distance learning modules. While such virtual English as Foreign Language (EFL) classes have undoubtedly played a pivotal role to ensure continuation of tertiary level teaching and learning even amidst the closure of educational institutions in the country, however, some contemporary research and news in this regard have reported on tertiary level learners’ dissatisfaction and reduced performances in such EFL classes. As such, to assess the learners’ perceived motivation and engagement in virtual EFL classes, the current research uses a mixed method approach. Here, the researcher uses  questionnaire survey, interview and FGD guidelines, constructed based on Vroom’s expectancy theory of motivation and instruments to assess attitude orientation, to collect data from both the “target” group, i.e. the learners, and the “resource” group, i.e. the teachers and the parents, from 5 tertiary level institutes of the country. Here, the data highlights negative attitude and reduced motivation orientation of the learners towards certain aspects in online EFL classes. The findings also manifest some imperial causal factors, which leads to reduced motivation and engagement of learners in such online modules. It unravels how online education has exacerbated the digital divide among the learners amidst the pandemic crisis. Moreover, the study also presents some pedagogic participant-centric suggestions to promote motivation and engagement of the learners in online EFL classes in a developing country context like Bangladesh.